HYPOTHESIS TESTING BY USING COUNTING PULSA ANALYSIS OF VARIANCE ONE DIRECTION WITH TURBO PASCAL PROGRAMMING LANGUAGE IN VERSION 7.0 WITH CV. ASTRINDO BUANA - Yuni Tribrasita; Ir. Aqwam Rosadi Kardian. MM (Jurnal Sistem Informasi, 2001)
Writing is about using the pulse counting method, one-way analysis of variance. Theauthor explains how to count the pulses with a few samples using One Way Analysisof Variance. In a one-way analysis of variance method, we may conclude whether thehypothesis that we are doing is acceptable or not. In this case the authors take thepulse on the sample CV. Astrindo Buana. At the end of writing, the attached programto better facilitate the calculations.